THE OFIOLITE COMPLEX AS SUPPORTED OF NATIONAL GEOPARK OF MERATUS MOUNTAIN, SOUTH KALIMANTAN - Setiawan, Jatmika; Nugroho, Nur Arief; Isharwanto, Isharwanto; Mustofa, Ali (Universitas Pembangunan Nasional Veteran Yogayakarta, 2021)
The Meratus Mountain in South Kalimantan Province have many geosites variations as geodiversity of National Meratus Mountain Geopark with theme the oldes ofiolite in Indonesia. Meratus Mountain was formed since 200-150ma from collision interaction of eastern part of Sunda Land with Pasternoster Continent who striking towards NE-SW in South Kalimantan Province. This mountain bordered Asam-asam Basin inthe eastern and Barito Basin in the western. The process of multideformation process formed the Meratus Mountain and exposed the ofiolite complex in Indonesia, aged between 200-150 million year ago. This rocks include : dunite, peridotite, pyroxenite, gabro, pillow basalt and chert.